Faktor-faktor yang mempengaruhi tekanan kerja semasa pandemik covid-19 dalam kalangan penolong pegawai perubatan dan Jururawat di fasiliti kesihatan di Utara Malaysia - Ku Muhammad Yasir, Ku Ibrahim (2020)
The COVID-19 pandemic has caused healthcare workers such as Assistant Medical Officers (AMO) and Nurses to become depressed, especially who involved in the screening, treatment, and care of patients who have been infected with COVID-19. However, not many studies have been conducted to assess the stress before and during COVID-19. The objective of this study was to identify the factors influencing work stress among AMO and Nurses working in health facilities in northern Malaysia during the COVID-19 pandemic. Correlation test done using SPSS 26. Results of the test show that there is a significant positive correlation between work stress and 3 variables during COVID-19, workload r = 0.504, supervisor support r = 0.294 and role of conflict r = 0.515. The conclusions drawn from this study have proven that workload, supervisor support and role of conflict affect level of work stress during COVID-19.